Memorandum of Understanding between the United Nations Children's Fund (UNICEF) and BRAC University for the project " Review of maternal, new born and child health projects currently implemented by UNICEF to recommended a single optimum MNCH model" (2012) - United Nations Children' Fund (UNICEF); BRAC University (United Nations Childredn's Fund and BRAC University, 2013)
United Nations Children's Fund (UNICEF) wishes to enter into an institutional contract with BRAC University , BRAC Centre Dhaka, 1212 Bangladesh for the provision of the certain services as stipulated in the attached document.